Against psycho-physical dualism. An Analysis and comparison of George Lakoff's and John Searle's accounts - Milewski, Daniel (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
This paper discusses John Searle’s biological naturalism and George Lakoff’s embodied mind hypothesis. These theories are presented as examples of a certain part of the philosophy of mind that breaks with the tradition launched by Descartes. In both cases, the break from this tradition is indicated to be a radical one as the theories argue not only against Cartesian dualism - the basic philosophical categories utilized by Descartes are being questioned. This attempt of departure from distinctions that seem to form a great part of the contemporary philosophy of mind may stand for a chance to provide a new perspective for some old philosophical problems.